Dry season aerosol iron solubility in tropical northern Australia - Winton, V.; Edwards, Peter; Bowie, A.; Keywood, M.; Williams, A.; Chambers, S.; Selleck, P.; Desservettaz, M.; Mallet, M.; Paton-Walsh, C. (Copernicus GmbH, 2016)
© Author(s) 2016.Marine nitrogen fixation is co-limited by the supply of iron (Fe) and phosphorus in large regions of the global ocean. The deposition of soluble aerosol Fe can initiate nitrogen fixation and trigger toxic algal blooms in nitrate-poor tropical waters. We present dry season soluble Fe data from the Savannah Fires in the Early Dry Season (SAFIRED) campaign in northern Australia that reflects coincident dust and biomass burning sources of soluble aerosol Fe. The mean soluble and total aerosol Fe concentrations were 40 and 500 ng m-3 respectively. Our results show that while biomass burning species may not be a direct source of soluble Fe, biomass burning may substantially enhance the solubility of mineral dust. We observed fractional Fe solubility up to 12% in mixed aerosols. Thus, Fe in dust may be more soluble in the tropics compared to higher latitudes due to higher concentrations of biomass-burning-derived reactive organic species in the atmosphere. In addition, biomass-burning-derived particles can act as a surface for aerosol Fe to bind during atmospheric transport and subsequently be released to the ocean upon deposition. As the aerosol loading is dominated by biomass burning emissions over the tropical waters in the dry season, additions of biomass-burning-derived soluble Fe could have harmful consequences for initiating nitrogen-fixing toxic algal blooms. Future research is required to quantify biomass-burning-derived particle sources of soluble Fe over tropical waters.